Translation And Comparative Analysis Of Tourism Terminology In Uzbek And English (Eurasian Journal of Learning and Academic Teaching, 2026)
This article examines the formation and development of tourism terminology in Uzbek and English and provides a comparative analysis of their translation features. In the context of globalization, the rapid growth of the tourism industry has expanded cultural, economic, and communicative interactions among countries, leading to the continuous development of tourism-related terminology. English, as one of the dominant languages of international tourism and scientific communication, plays an important role in the creation and dissemination of tourism terms. As a result, many tourism terms are borrowed and adapted into other languages, including Uzbek. The study analyzes the semantic, lexical, and structural characteristics of tourism terminology using a comparative approach. Particular attention is given to translation strategies such as equivalence, adaptation, descriptive translation, and calque. The findings show that English tourism terminology has an international character and morphological flexibility, while in Uzbek the adaptation of terms to the national linguistic system and the preservation of semantic clarity are important. The results contribute to terminology studies, translation theory, and comparative linguistics.